A case of an upper anterior abdominal wall extra-skeletal Ewing sarcoma- soft tissue reconstruction with medial intercostal artery perforator flap and free anterolateral thigh fasciocutaneous flap with arteriovenous loop graft. (January 2022) - Liu, Y.; Subramaniam, S.; Sasidaran, R.; Ruhana, A.A.H.; Jimeno, Z.K.L.
Abstract: Introduction: Extra-skeletal Ewing sarcoma - a rare clinical entity. After the tumour resection, a huge upper anterior abdominal wall defect poses a challenge in soft tissue reconstruction in a thin individual. Case presentation: We report an anterior abdominal wall Ewing sarcoma in a 22-year-old gentleman, arising from the left rectus abdominis muscle. After wide local excision, the reconstruction was achieved with free anterolateral thigh(ALT) fasciocutaneous flap with arteriovenous(AV) loop graft, right medial intercostal artery perforator(MICAP) flap and split-thickness skin graft(SSG). Discussion: The goals of anterior abdominal wall reconstruction are to restore the integrity of the abdominal wall, prevent visceral eventration, and provide functional support. In view of the size of the defect, a free ALT flap was harvested and anastomosed to the left deep inferior epigastric bundle with the AV loop graft. Although the current trend is skewed towards the use of biologic mesh, an on-lay prolene mesh was used due to its affordable cost and that the biologic mesh was not available in Malaysia. The options of further reconstruction after the patient developed marginal flap necrosis and surgical site infection were also discussed. Post-operation 3 months, there was denser hair growth on the ALT flap. This finding has never been reported before and warrants further studies. Conclusion: The use of combination of various technique, namely free ALT fasciocutaneous flap with AV loop graft, right MICAP flap and SSG in reconstruction ensures a satisfactory functional and aesthetic outcome in the upper anterior abdominal wall reconstruction. Highlights: Extra-skeletal Ewing sarcoma is a rare clinical entity. The goals of anterior abdominal wall reconstruction are to restore the abdominal wall integrity, prevent visceral eventration, and provide functional support. Mesh reinforcement with overlying myofascial coverage is preferred as a first-line option in anterior abdominal wall reconstruction.